Farming Risks and Security Challenges in Vegetable Production in Orlu, Imo State - E., Osuji, E.; Ehirim, N.C.; Rahji, M.A.Y; Awoyemi, T.T.; Salman, K.K.; Odii, M.A.C.A; Onyemuwa, S.C.; B., Ibeagwa, O.; Chikezie, C.; Okwara, M.O. (Asian Development Policy Review, 2017)
Farming risk is a security challenge that reduces the actual outcome from farmers expected outcome. Predominant farming risk is the reason for deviations from planned production in Imo State. Food supply gap becomes reduced if the farming risk associated with vegetable production is reduced and the effect on output increased through this study. A total of 152 farmers from 10 communities across three (3) local government areas of Orlu agricultural zone were used for data analysis. Data were obtained using a well-structured questionnaire and analyzed using descriptive statistics and econometric tools. Majority (98.7%) and (94.7%) of farmers planted fluted pumpkin, bitter leave respectively in a mixed cropping pattern to withstand risk and security challenges with 96.7% and 95.4% of them adopting correct planting distances and soil fertility amendments as copping strategies. The perceived risk intensity equation showed the linear model as the best fit with F-statistics of 15.182, greater than its tabulated value of 4.689 at p ‹ 0.05 critical value, hence the lead equation. The model has only 5 significant explanatory variables at p ‹ 0.05 with a co-efficient of multiple determination of 0.697, implying that 69.7% of the total variations in perceived farming risk intensity in vegetable production in the area were due to the included explanatory variables. Farmers perceived risk intensity increased significantly by 0.212%, 3.60% and 0.735% with a unit increase in farmer’s age, access to credits and household size respectively but decrease significantly by 5.87% and 2.6X10-6% with a unit decrease in risk mitigation measures and income at p ‹ 0.05 critical levels. Intensifying risk mitigation measures and encouraging younger vegetable farmers in vegetable production in the area can reduce farming risk in the area.